Development of Non-bank Financial Institutions and Capital Markets in European Union Accession Countries - Bakker, Marie-Renée; Gross, Alexandra (Washington, DC: World Bank, 2013)
This paper assesses the role of non-bank financial institutions and capital markets in the financial sectors of the eight first-wave of Eastern European EU accession countries (the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia), the current state of development and prospects for future growth, and the likely impact on these segments of the financial system of accession to the EU. Throughout the paper, the level of development of nonblank financial institutions and capital markets in the accession countries is benchmarked against comparable development levels seen in existing EU member states. The paper concludes with a series of policy recommendations to facilitate future development of non-bank forms of financial intermediation.